Pengaruh profitabilitas (ROE) dan leverage (DER) terhadap pembayaran dividen (DPR) pada perusahaan-perusahaan property and real estate - Iwan Kurniawan; Ardi Paminto; Maryam Nadir (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
Iwan Kurniawan, Influence Profitability (ROE) and Leverage (DER) Against Payment of Dividends (DPR) On Property and Real Estate Company Listed in Indonesia Stock Exchange. Supervisor: Ardi Paminto and Maryam Nadir.The purpose of this study was to determine the effect of Return on Equity and Debt to Equity Ratio of Dividend Payout Ratio in the Company which is  engaged in property and real estate listed on the Indonesia Stock Exchange.Results of research and discussion shows indicate that free variable affect very weak bound variable regression coefficient value of 0346. On profitability and leverage variables simultaneously significant effect on dividend payments for property and real estate companies. This is evidenced by the results of the F test, simultaneously independent variables affect the dependent variable with a significance level under 0.05, which means that the independent variable has  significant effect on the dependent variable. And Partially (alone), variable profitability has significant effect on dividend payments and variable leverage hasn’t significant effect on dividen Payment on the Property and Real Estate Companies Listed on the Stock Exchange of Indonesia Year 2010-2014. This study uses secondary data financial ratios  on property and real estate company listed on the Indonesia Stock Exchange in period 2010-2014. Data analyzed with regression model and using the computer program SPSS 21.Keywords: Profitability, Leverage and Dividend Payment